Vocabulary Language Prediction (VLP) to Enhance Students' Reading Achievement in Narrative Text - Linda C Dengah; Dzulfikri; A Wiqoyil Islama (Universitas Tidar, 2022)
Reading comprehension plays a vital role in entertaining and gaining some information. The teacher-researcher needs to do a pre-reading activity to scaffold students' reading comprehension in narrative text. VLP (Vocabulary, Language, Prediction) is an appropriate strategy to improve students' reading achievement by mastering vocabulary before the main reading activity. The students in grade X of SMK with low English reading achievement were taught English, especially reading comprehension in narrative text. Before the strategy was implemented, the average score was 41.1. Then, the Classroom Action Research was conducted, and the VLP strategy was applied. After implementing two cycles of CAR, the average score reached 77.8. It proves that by applying the VLP strategy, students can improve their reading comprehension. Students' motivation in learning English also increased as well as their self-confidence to express their thoughts in class discussions.